2010
DOI: 10.21273/hortsci.45.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Bispyribac–sodium, Sulfosulfuron, and Interseeding Creeping Bentgrass for Long-term Control of Roughstalk Bluegrass

Abstract: Roughstalk bluegrass (Poa trivialis L.) contamination is problematic on golf course fairways from the Midwest to the mid-Atlantic regions of the United States. Bispyribac–sodium and sulfosulfuron have potential to selectively control roughstalk bluegrass. Our objectives were to determine the most effective herbicide treatments for short- and long-term roughstalk bluegrass control and to determine if interseeding with creeping bentgrass (Agrostis stolonifera Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…1). Turf quality and percent cover averaged across harvest dates and years was highest for L93 followed by Laser and then Pulsar (Table 1), which was similar to that reported previously (Morton et al, 2009;Rutledge et al, 2010a). However, RBG cover never fell below 90% over the growing seasons of our study, which was less dramatic than those observed by Morton et al (2009), where cover of untreated Pulsar fell below 20% after intense summer stress while Laser maintained >90% cover (Morton, 2008).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…1). Turf quality and percent cover averaged across harvest dates and years was highest for L93 followed by Laser and then Pulsar (Table 1), which was similar to that reported previously (Morton et al, 2009;Rutledge et al, 2010a). However, RBG cover never fell below 90% over the growing seasons of our study, which was less dramatic than those observed by Morton et al (2009), where cover of untreated Pulsar fell below 20% after intense summer stress while Laser maintained >90% cover (Morton, 2008).…”
Section: Resultssupporting
confidence: 88%
“…Mean daily maximum temperatures in Morton et al (2009) in July were 29.3°C compared to 28.3 and 26.0°C in 2008 and 2009 of our study, respectively. Furthermore, signifi cant damage occurred in RBG in our previous studies (Rutledge et al, 2010a) with 20 or more days per growing season with maximum daily temperatures ≥30°C while highs reached ≥30°C on only 7 and 12 d during the growing seasons of 2008 and 2009, respectively ( Fig. 1).…”
Section: Resultsmentioning
confidence: 68%
“…This difference in high temperature tolerance results in areas of stressed, dormant, or dead RBG throughout mixed stands of RBG and CBG during supra‐optimal temperatures, therefore relegating RBG to a weed in CBG fairways. Herbicides including bispyribac‐sodium and sulfosulfuron selectively control RBG in CBG (McCullough and Hart, 2006; Morton et al, 2009; Rutledge et al, 2010a). Control of RBG as well as injury to CBG from these herbicides is dependent on ambient temperature (Lycan and Hart, 2006; McCullough and Hart, 2006; Rutledge et al, 2010a).…”
mentioning
confidence: 99%
“…Herbicides including bispyribac‐sodium and sulfosulfuron selectively control RBG in CBG (McCullough and Hart, 2006; Morton et al, 2009; Rutledge et al, 2010a). Control of RBG as well as injury to CBG from these herbicides is dependent on ambient temperature (Lycan and Hart, 2006; McCullough and Hart, 2006; Rutledge et al, 2010a). The relatedness of temperature to both decline and control of RBG makes understanding its physiology under high temperatures critical for maximizing control or improving management techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation